Wave resource assessment and wave energy exploitation along the Indian coast. (1st December 2020) - Patel, Ravi P.; Nagababu, Garlapati; Arun Kumar, Surisetty V.V.; M., Seemanth; Kachhwaha, Surendra Singh
Abstract: The present study investigates the feasibility of wave energy exploitation along the Indian coast using 19-year (2000–2018) hindcasted wave data generated by WAVEWATCH-III with a fine spatial resolution (0.1° × 0.1°) and temporal resolution (6 h). The wave model is validated against 12-month measured wave data collected at multiple buoy sites and compared with 19-year ERA5 data across the study area. The results show good agreement between model data and the other two datasets. The spatio-temporal variability analysis of wave energy flux reveals that southern coast of India has the mean wave energy flux ranging from 6 to 10 kW/m with a minimum monthly (<2.0), seasonal (<1.0) and annual (<0.2) variability which could be a promising area for future wave energy exploitation. A detailed analysis of wave power resource has been discussed for nine hotspot locations which were selected based on the optimum hotspot index, geographical restrictions on bathymetry and distance to the shore. Further, each hotspot has been analysed through combined scatter and energy diagrams. Finally, electrical power output is estimated at each hotspot using five wave energy converters and observed that the annual energy production at most of the locations is above 800 MWh with more than 70% availability. Highlights: Comprehensive assessment of wave energy using 19-year WAVEWATCH III modelled data. Spatial and temporal variability of wave energy flux is analysed. Identified optimal hotspots for wave energy exploitation based on OHI, bathymetry and distance from shore. Wave parameter characterization at hotspots using combined scatter and energy and wave rose diagrams. Wave power estimation using five commercial wave energy converters.